Wie man wirklich zuh̲rt (Assemble You, 2022)
Welcome to our Assemble You Learning Podcast How many times have you had a conversation that just ... didn't feel right? People listen to you, but not really. If you're honest with yourself, how many times have you actually been the one person who wasn't really listening? Poor listening leads to mistakes and misunderstandings. This can lead to ineffective decisions and costly mistakes in business life. If you're not listening properly, you might miss out on fantastic suggestions from people you might even have hired yourself. And on a personal level, if you don't listen properly, you can hurt feelings, which can lead to a loss of team cohesion. In this module we will teach you techniques that will improve your listening skills. Learning Outcomes Learn about the disadvantages of poor listening and how people generally listen inefficiently. Learn tricks to significantly improve listening skills.